1982
DOI: 10.1084/jem.155.5.1452
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Dw2: a genetic marker for human immune response to short ragweed pollen allergen Ra5. II. Response after ragweed immunotherapy.

Abstract: In the preceding paper (1), we reported a significant striking association between Dw2 and IgE and IgG antibody (Ab) 1 responses to Ra5 in ragweed-allergic Caucasian subjects as a result of natural exposure to ragweed pollen. The question arose as to whether this relationship might change after parenteral immunization with much higher dosages of ragweed antigens. Such treatment, known as immunotherapy or hyposensitization, is commonly administered to ragweed-allergic patients to alleviate their allergic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 18 publications
2
43
0
1
Order By: Relevance
“…The difference in responsiveness was correlated with the H-2 genotype of the strain. Marsh et al 32 have suggested that the enhanced IgE response to highly purified pollen allergens such as antigen E and Ra5 is associated with a particular HLA haplotype. In the present study, however, none of the SAR traits, OG-specific IgE levels, or total serum IgE levels showed positive linkage to 6p21, which is where the HLA genes are located.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in responsiveness was correlated with the H-2 genotype of the strain. Marsh et al 32 have suggested that the enhanced IgE response to highly purified pollen allergens such as antigen E and Ra5 is associated with a particular HLA haplotype. In the present study, however, none of the SAR traits, OG-specific IgE levels, or total serum IgE levels showed positive linkage to 6p21, which is where the HLA genes are located.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of several genes has been proposed. The genes include those specific to the allergen, particularly MHC class II molecules from chromosome 6 [1, 2, 3] involved in antigen presentation and the α chain of the T cell receptor, encoded on chromosome 14q11 [4]. In addition, a strong genetic linkage was reported for the IL-4 gene cluster on chromosome 5, involved in B cell activation [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of TDI-induced asthma is still unknown but recent evidence suggests an immunological mechanism [4]. In fact, TDI-induced asthma and extrinsic asthma have a similar pattern of inflammatory cell infiltration in bronchial biopsies [5,6]; inhalation challenge with TDI causes an increase in circulating CD8+ lymphocytes and eosinophils in sensitized subjects [7]; and an association with human leucocyte antigen (HLA) class II genes is documented both in TDIinduced asthma [8] and in allergen-induced asthma [9,10].…”
mentioning
confidence: 99%